Development of E-Comic-Based Learning Media Using Pixton in Theme 7 Sub-theme 2 in Class V SDN 101775 Sampali T.A 2022/2023 - Nurmayani; Yunita Sari Sinaga (Indonesian Journal of Advanced Research, 2023)
The purpose of this research is to produce a learning media in the form of E-Comic using Pixton which is feasible, effective and practical. The type of research used is research and development (R&D) which has a 4D development model developed by Thiagarajan namely Define, Design, Develop, and Disseminate. The instruments used to collect data were teacher interviews, material and media validation questionnaires, educational practitioner (teacher) questionnaires, and test questions for students. The results of this study show that the validation of media experts gets a percentage of 97.27% after revision with the "Very Eligible" category. Material expert validation by getting a percentage of 96.47% in the "Very Eligible" category. In terms of practicality, this Pixton-based E-Comic learning media is considered practical which is assessed by educational practitioners with a percentage of 92.72% in the "Very Practical" category. Then. The level of effectiveness of this learning media can be seen from the results of the students' pre-test and post-test scores. The pre-test score showed effectiveness only at 46.23% in the "Ineffective" category while the post-test score increased to 81.61% in the "Effective" category. Based on this, it can be concluded that E-Comic based learning media using Pixton is declared feasible, practical and effective to be applied in the learning process in schools.